2022
DOI: 10.1111/cns.13902
|View full text |Cite
|
Sign up to set email alerts
|

Rab27a‐dependent exosomes protect against cerebral ischemic injury by reducing endothelial oxidative stress and apoptosis

Abstract: Introduction: Multicellular crosstalk within the brain tissue has been suggested to play a critical role in maintaining cerebral vascular homeostasis. Exosomes (EXs) mediated cell-cell communication, but its role in cerebral ischemic injury is largely unknown.Rab27a is one of the major genes controlling EX release. Here, we explored the role of Rab27a in regulating brain EXs secretion, and the effects of Rab27a-mediated EXs on ischemia evoked cerebral vascular disruption and brain injury.Methods: Cerebral isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…35,37 While other strains exist, we present a novel strain on a C57BL/6J background. 38,39 Utilizing the CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeat–associated 9) technology, we created novel Rab27a global and conditional null strains by targeting exon 4, which is the first conserved exon among known Rab27a transcripts (Figure S1A). In vitro validation of the designed single guide RNA was performed to identify selectivity in genomic targeting of these regions within the Rab27a sequence before microinjection (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…35,37 While other strains exist, we present a novel strain on a C57BL/6J background. 38,39 Utilizing the CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeat–associated 9) technology, we created novel Rab27a global and conditional null strains by targeting exon 4, which is the first conserved exon among known Rab27a transcripts (Figure S1A). In vitro validation of the designed single guide RNA was performed to identify selectivity in genomic targeting of these regions within the Rab27a sequence before microinjection (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…This cellular process can be initiated either by the extrinsic death receptor pathway or the intrinsic mitochondrial pathway, both ultimately leading to the activation of executioner caspases. Dysregulation of apoptotic signaling and oxidative stress‐induced vascular injury and integrity disruption play a pivotal role in the initiation and development of IS and contribute to neuronal cell death and BBB disruption after ischemic stroke and recanalization therapy 113 . Excessive endothelial apoptosis is implicated in worse outcomes and hemorrhagic transformation following thrombolysis In MCAO mice, miR‐503 level was significantly increased in brain and contributed to endothelial cell (EC) dysfunction by promoting apoptosis.…”
Section: Endothelial Cell Death Pathwaysmentioning
confidence: 99%
“…Dysregulation of apoptotic signaling and oxidative stress‐induced vascular injury and integrity disruption play a pivotal role in the initiation and development of IS and contribute to neuronal cell death and BBB disruption after ischemic stroke and recanalization therapy. 113 Excessive endothelial apoptosis is implicated in worse outcomes and hemorrhagic transformation following thrombolysis In MCAO mice, miR‐503 level was significantly increased in brain and contributed to endothelial cell (EC) dysfunction by promoting apoptosis. While inhibition of miR‐503 ameliorated apoptosis of ECs, oxidative stress, BBB permeability, and neurological damage after stroke.…”
Section: Endothelial Cell Death Pathwaysmentioning
confidence: 99%
“…In a study by Ma et al, RAB27A was found to be an important regulator of EV secretion in the brain, which further provides protection against cerebral ischemia in an ischemic stroke mouse model. Brain-derived EVs obtained from RAB27A knockout mice also fail to attenuate ischemic injury in vivo, which implies that the RAB27A-dependent secretion of EVs may be critical to brain functioning [269]. Another study revealed that the siRNA-mediated knockdown of RAB27A attenuates hair growth in vitro [270].…”
Section: Genetic Modification Of Genes Implicated In Ev Biogenesis An...mentioning
confidence: 99%